Effect of propinox and pinaverium bromide on ex vivo colonic motor patterns and their synergistic effect with hyoscine butyl bromide - Traserra, Sara; Alcalá-González, Luis Gerardo; Barber, Claudia; Landolfi, Stefania; Malagelada, Carolina; Lange, Robert; Appelqvist, Terence; Corsetti, Maura; Jimenez, Marcel (Frontiers in Pharmacology, 2025)
BackgroundAntispasmodic agents are used to treat abdominal pain. The mode of action of pinaverium bromide and propinox in the colonic tissue has never been characterized. This study aimed to explore whether HBB can complement the antispasmodic effects of these drugs.MethodsColon samples were procured from the macroscopically normal regions of 33 patients undergoing colon cancer surgery and subjected to muscle bath experiments. Pinaverium bromide and propinox alone and in combination with HBB were assessed under the following conditions: (1) spontaneous phasic contractions (SPCs) induced by isometric stretch (with 1 µM tetrodotoxin); (2) contractility induced by 10–5 M carbachol; (3) the electrical field stimulation (EFS) of the excitatory pathway (in the presence of 1 mM Nω-nitro-L-arginine and 10 µM MRS2179); and (4) an EFS-induced selective excitation of the inhibitory pathway (under nonadrenergic, noncholinergic pharmacological conditions). An isobolographic study was performed to evaluate the possible interaction between pinaverium bromide, or propinox and HBB.ResultsPinaverium bromide and propinox concentration-dependently reduced SPC (10–5 M: 29%–47% reduction) in both muscle layers. Carbachol-induced contractions were partially reduced by pinaverium bromide (10–5 M: 37%–46% reduction) and propinox (10–5 M: 32%–44% reduction) and almost totally inhibited by the combination with HBB. EFS-induced contractions were slightly decreased by pinaverium bromide (10–5 M; circular muscle: 39% reduction, but no effect on longitudinal muscle) and propinox (10–5 M: circular 48% and longitudinal 37%), and to a greater extent, by the combination with HBB. Both pinaverium bromide (10–5 M: 11%) and propinox (10–5 M: 42%) reduced the EFS-induced off-response but not the on-relaxation. The interaction index measured for the combined activity of HBB with pinaverium bromide or propinox was less than 1 in SPC, carbachol-induced contractions, and EFS-induced contractions.ConclusionThe pharmacological profile obtained in this study was consistent with an L-type calcium channel blocker for both pinaverium bromide and propinox, with an unlikely or a weak antimuscarinic effect for the latter. When combined with the antimuscarinic agent HBB, both pinaverium bromide and propinox showed a synergistic inhibition of contractile responses. This finding could have clinical implications, suggesting a combination treatment approach for greater therapeutic benefits.